Alunos indígenas da educação superior do Maranhão: entre os caminhos de ações afirmativas e trilhas de diálogos interculturais - LOPES, Márcio Ronald (2023)
Resisting to exist was and is the motto of indigenous peoples. Thus, the struggles for their rights as citizens, from specific and differentiated cultures, are already part of Brazilian legislation. Among others, we highlight the guarantee of education at all levels of education, respecting the learning processes of each people. This research analyzes the access and retention challenges faced by indigenous students in Higher Education in the cities of Imperatriz and Grajaú, in the state of Maranhão. This research is based on a qualitative approach, as it provides an opportunity to understand the meanings attributed by participants in specific contexts. Indigenous students from the Federal University of Maranhão – Imperatriz and Grajaú contributed to the research. Students from the National Basic Education Teacher Training Plan – PARFOR participated in the latter. The research was also carried out at the Faculty of Education Santa Terezinha – FEST. We used the interview as an instrument to analyze the challenges in access and retention of indigenous students in the aforementioned institutions. The research pointed out that the struggles waged by indigenous peoples from other South American countries, such as Colombia, Peru, Mexico and Bolivia, to exercise their right to formal education contributed to the historical context of indigenous educational policies in Brazil. Studies during the research showed that, although the quota policy for indigenous people exists, not all HEIs in Brazil have a policy that includes indigenous students in accessing and remaining at Universities. The research showed that the HEIs surveyed have affirmative actions aimed at supporting indigenous students, whether in the stages of admission to graduation, entrance exams and monitoring of notices, or with financial and pedagogical support during the course periods. Finally, the existence of prejudice, discrimination and racism faced by indigenous students in the academic environment was highlighted, as well as the way they deal with this reality, seeking to (re)construct and (re)signify their identities.